Herpes Zoster Vaccine Response in Inflammatory Bowel Disease Patients on Low-dose Immunosuppression. Issue 6 (June 2016) - Wasan, Sharmeel K.; Zullow, Samantha; Berg, Adam; Cheifetz, Adam S.; Ganley-Leal, Lisa; Farraye, Francis A.
Abstract : Background: Inflammatory Bowel Disease (IBD) patients are at an increased risk of developing herpes zoster (HZ), especially when immunosuppressed. HZ may be preventable with the herpes zoster vaccine (HZV), but many patients are not offered vaccination over concern regarding efficacy and fear of adverse events. Although the Center for Disease Control and Prevention recommends that low-dose immunosuppression is not a contraindication, few IBD patients on these medications are receiving HZV. Methods: This study was a prospective clinical trial to assess the safety and immunogenicity of HZV among 2 groups of IBD patients. Group A consisted of 14 patients on low-dose immunomodulators and group B consisted of 25 patients either on 5-aminosalicylic acid or no IBD therapy. Blood samples were obtained to measure immune responses. Results: HZ specific immunoglobulin G rose significantly in both groups but the response was lower in the immunosuppressed group ( P = 0.0002). Peripheral blood mononuclear cell secretion of Tumor necrosis factor-α in response to HZ antigen increased after HZV in group B, but not in group A. Interleukin-8 secretion increased in both groups, but the response was much higher in group B. There were no significant differences in adverse events between groups. No patients developed a HZ-like rash within 1 year after vaccination. Conclusions: IBD patients on low-dose immunosuppressive therapy have a blunted immune response to HZV as compared with nonimmunosuppressed subjects. Despite this, immunosuppressed IBD patients are able to mount a statistically significant immune response. There were no serious adverse events to HZV. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 8 April 2016.